2021
DOI: 10.3390/ijms222111638
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Controls IL-23 Production by Human Monocytes

Abstract: C-reactive protein (CRP) is an acute-phase protein in humans that is produced in high quantities by the liver upon infection and under inflammatory conditions. Although CRP is commonly used as a marker of inflammation, CRP can also directly contribute to inflammation by eliciting pro-inflammatory cytokine production by immune cells. Since CRP is highly elevated in serum under inflammatory conditions, we have studied the CRP-induced cytokine profile of human monocytes, one of the main innate immune cell populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Serum IL-23 levels were significantly elevated in patients with SLE compared to healthy individuals and correlated with overall SLE disease activity as measured by SLEDAI [60]. Furthermore, the increased c-reactive protein levels observed in inflammatory conditions, especially during flares of the disease can be linked specifically with the IL-23 production in monocytes [58]. Despite the recently published phase 3 trial [33,34], our findings indicate that the IL-12/IL-23 inhibitor "ustekinumab" may efficiently disrupt the molecular interaction network of monocytes and therefore some patients might indeed benefit from this drug.…”
Section: Discussionmentioning
confidence: 91%
“…Serum IL-23 levels were significantly elevated in patients with SLE compared to healthy individuals and correlated with overall SLE disease activity as measured by SLEDAI [60]. Furthermore, the increased c-reactive protein levels observed in inflammatory conditions, especially during flares of the disease can be linked specifically with the IL-23 production in monocytes [58]. Despite the recently published phase 3 trial [33,34], our findings indicate that the IL-12/IL-23 inhibitor "ustekinumab" may efficiently disrupt the molecular interaction network of monocytes and therefore some patients might indeed benefit from this drug.…”
Section: Discussionmentioning
confidence: 91%
“…Patel et al (68) showed that IL-17 stimulates CRP expression in hepatocytes and coronary artery smooth muscle cells and mediates CRP induction via p38 MAPK and ERK1/2-dependent NF-ĸB and C/EBPβ activation independently of IL-1β and IL-6. Moreover, a recent study showed that CRP increased IL-23 production by promoting gene transcription of IL23A (69). However, these studies cannot explain the increased expression of these cytokines under conditions of extremely low hs-CRP concentrations.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to elevated IL-10 levels, TNF-α and IL-23 were also increased in serum of COVID-19 patients and correlated positively with CRP levels. It has been previously investigated that CRP can induce TNF-α and IL-23 production by monocytes ( 33 , 34 ), so the elevation of TNF-α and IL-23 in COVID-19 patients might be related to CRP-induced monocytes. IL-23, in turn, can promote Th17 proliferation and differentiation, which releases the pro-inflammatory cytokine IL-17 and enhances inflammation ( 35 ).…”
Section: Discussionmentioning
confidence: 99%